Cultural Based Tourism Development and Environmental Entrepreneurship - Kasmin; Sugiarto; Widianto, Nur; Herawan, Tutut (CV ODIS, 2023)
Culture-based tourism (Cultural Tourism) is a type of tourism activity that utilizes culture as a tourist attraction visited by tourists in these tourist destinations, tourists will feel and learn about certain cultures. The existence of cultural tourism can be used as an object of tourist attraction that can preserve cultural heritage. Cultural tourism is like a double-edged knife in the use of cultural heritage as a tourist attraction. On the one hand, tourism can preserve the cultural heritage, while on the other hand, tourism activities will damage or negatively affect the cultural heritage because the object will be consumed by tourists (Burn and Holden, 1995). To avoid the negative impact of tourism, good management of tourism is needed, especially in this case culture. If the tourism industry can be managed properly, tourism can ensure the preservation of nature and culture. In addition, tourism can also be a forum for employment for local people around the tourist area. Community empowerment development can be applied from several indicators, including increasing knowledge, increasing abilities/skills, and related to programs implemented by the government. This research uses the descriptive qualitative research method, meaning that data is collected through several stages; field observation, data collection, resource person interviews, documentation, and relevant literature review, The title of this study is Tourism Development based on Culture and Environmental Entrepreneurship and is a case study in